'I'm not a gastarbeiter anymore': liminal mobility of young Kazakh IT professionals in Russia. Issue 5 (3rd September 2018) - Feakins, Melanie; Zemnukhova, Liliia
ABSTRACT: In the past decade, Moscow, St Petersburg, and Kazan have become 'go to' destinations for IT specialists from Russia and Central Asia. The ethos of technical creativity and ingenuity, combined with the presence of science, technology and engineering universities, is generating a profound momentum in IT worlds. The vibrant technology communities are becoming magnets for enthusiasts seeking to thrive amongst others with similar devotions. One example is young people from Kazakhstan who are 'coming of age' and forging IT careers in these cities. We introduce the concept of 'liminal mobility' to explore their narratives. The key roles are played by: secondary schooling situations involving Kazakh-Turkish lyceums; joint Kazakh/Russian programs in mathematics, physics, and IT; and recruitment in dormitories for part-time jobs that became 'career-making' positions. The analysis points to the significance of these connections in making the discrepant knowledge mobilities that are the focus of this special issue.